Student's Perspective on Reading Comprehension Through E-Learning at Senior High School - Dahlia Novita Sari (INTERNATIONAL JOURNAL OF LANGUAGE PEDAGOGY, 2023)
ABSTRACT The research is a perspective on reading comprehension was carried out SMAN 14 Pekanbaru, the main focus of the study E-learning reading comprehension based on application whatsaap grub, stated that qualitative research is a research procedure that uses descriptive data in the form of written or oral words from people or actors that can be observed. This research was conducted online because the keeping up with didadvanced technologies not allow the researcher to go directly to the field and the subjects of this study were eleven-grade students. That is why the purpose of reading is to get some information from the text. Reading as one of the basic language skills has an important role in widening one's knowledge to access information and make meaning. In learning english, students are expected to get some messages from their reading. In reading, there are many kinds of reading text, such as narrative, recount, report, descriptive, explanation, analytical exposition, hortatory exposition, procedure, discussion, news item and so forth. The high level of enthusiasm for learning is not limited to age, gender or one’s occupation, many workers still want to study in the midst of their work activities. Limited time is an obstacle for workers whowant to take conventional courses. This problem can be answered by E-learning medias, E-learning utilizing technology for distance learning activities. And this study was aimed at analyzing the students, learn material E-learning reading comprehension use application whatsaap grub, on the analysis result the total average score in one class is 89,9%. From the results of the study it is known that the average the ability of students in learning to read and understand using the whatsapp grub application method is classified as very good. In this case, in this case, there are 20 (80%) students in the very good category, there are 4 (20%) students categorized as good and none categorized as low and bad.